1990
DOI: 10.1029/jb095ib02p01167
|View full text |Cite
|
Sign up to set email alerts
|

Seismic structure of the continental crust based on rock velocity measurements from the Kapuskasing Uplift

Abstract: The Michipicoten greenstone belt (MGB), Wawa gneiss terrane (WGT), and Kapuskasing structural zone (KSZ) in Ontario, Canada, are regarded as a 25‐km‐thick partial cross section through the crust of the Superior Province. We measured compressional wave velocities (Vp) at confining pressures up to 600 MPa for representative rock samples from these terranes. Vp for MGB is variable (6.1–7 km/s) and depends on composition and anisotropy. Compressional wave velocities for low anisotropy quartzofeldspathic gneisses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 54 publications
3
53
0
Order By: Relevance
“…Compressional-wave velocities were measured to confining pressures of 600 MPa for three mutually orthogonal cores (normal to foliation, perpendicular to lineation, and parallel to lineation) cut from each sample using the equipment and methods described in Fountain et al (1990). Densities (p) were determined for each core based on its mass and its volume (determined with a helium pycnometer).…”
Section: Laboratory Methods and Resultsmentioning
confidence: 99%
“…Compressional-wave velocities were measured to confining pressures of 600 MPa for three mutually orthogonal cores (normal to foliation, perpendicular to lineation, and parallel to lineation) cut from each sample using the equipment and methods described in Fountain et al (1990). Densities (p) were determined for each core based on its mass and its volume (determined with a helium pycnometer).…”
Section: Laboratory Methods and Resultsmentioning
confidence: 99%
“…Examples include the Canadian, Baltic, south African, and southern Indian shields (e.g., Weaver and Tarney 1984;Ashwal et al 1987;Fountain et al 1987Fountain et al , 1990Pinet and Jaupart 1987;Pinet et al 1991;Mareschal et al 2000a;Nicolayson et al 1981;Jones 1988;Roy and Rao 2003;Ray et al 2003;Rao et al 2003), the Ivrea-Verbano and Strona-Ceneri zones, southern Alps, Italy (e.g., Galson 1983), the Arizona Basin and Range (Sass et al 1994;Ketcham 1996) and the Sierra Nevada batholith (Brady et al 2006) in North America. A common occurrence in several of these crustal segments is the systematic metamorphic (structural) gradation from greenschist facies through amphibolite and granulite facies (e.g., Percival et al 1992), and the associated depletion in crustal radiogenic heat production with increase in metamorphic grade (e.g., Rudnick and Fountain 1995).…”
Section: Introductionmentioning
confidence: 98%
“…[11][12][13][14][15]). Vanorio et al [16] have previously reported P-and S-wave velocity data for volcanic rocks, including some from Etna.…”
Section: Introductionmentioning
confidence: 99%